2017
DOI: 10.1371/journal.pone.0185737
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study on novel blood containers with alternative plasticizers for red cell concentrate storage

Abstract: Di (2-ethylhexyl) phthalate (DEHP), a typical plasticizer used for polyvinyl chloride (PVC) blood containers, is eluted from the blood containers and exerts protective effects on red blood cells. However, a concern for detrimental effects of DEHP on human health has led to the development of potential DEHP substitutes. Here, we compared the red blood cell preservation ability of two types of non-DEHP blood containers with safe alternative plasticizers to that of DEHP blood containers. Red cell concentrates in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…Lagerberg et al showed an increasing plasticizer concentration along the storage of RBC (from D1 to D42) ranging from 4.1 ± 0.9 to 33.0 ± 11.0 μg/mL for DEHP and from 0.2 ± 0.1 to 4.5 ± 0.9 μg/mL for DINCH [4]. The same observation was noted by Morishita et al during the storage of RBC in PVC‐DEHP bags with DEHP concentrations from 2.60 ± 0.72 μg/mL to 22.0 ± 4.4 μg/mL at D1 and D42, respectively [31]. Our study highlights the same phenomenon for DEHT in RBC, namely, a concentration increases from 0.50 ± 0.46 to 7.12 ± 0.74 μg/mL, along the storage period.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Lagerberg et al showed an increasing plasticizer concentration along the storage of RBC (from D1 to D42) ranging from 4.1 ± 0.9 to 33.0 ± 11.0 μg/mL for DEHP and from 0.2 ± 0.1 to 4.5 ± 0.9 μg/mL for DINCH [4]. The same observation was noted by Morishita et al during the storage of RBC in PVC‐DEHP bags with DEHP concentrations from 2.60 ± 0.72 μg/mL to 22.0 ± 4.4 μg/mL at D1 and D42, respectively [31]. Our study highlights the same phenomenon for DEHT in RBC, namely, a concentration increases from 0.50 ± 0.46 to 7.12 ± 0.74 μg/mL, along the storage period.…”
Section: Discussionsupporting
confidence: 67%
“…Number of replicates for each condition: n = 3. *Statistically different ; **non-statistically different.± 4.4 μg/mL at D1 and D42, respectively[31]. Our study highlights the same phenomenon for DEHT in RBC, namely, a concentration increases from 0.50 ± 0.46 to 7.12 ± 0.74 μg/mL, along the storage period.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…This study also reported a higher rate of osmotic fragility, as well as decreased deformability when storing in BTHC and DINCH. Yet another study [7], also using SAGM, found no differences when comparing haemolysis between DEHP and a di (2‐ethylhexyl) 4‐cyclohexene‐1,2‐dicarboxylate (DOTH)/DINCH combination. In this study, baseline haemolysis rate (t = 0) was, however, already substantial (0.4%), while some units were close to exceeding 0.8% haemolysis in the third week of storage, which is the maximum amount of haemolysis that European countries adhere to in their guidelines when storing up to 6 weeks (Guide to the preparation, use and quality assurance of blood components, EDQM, 2020).…”
Section: Rationale For Required Quality and Process Parameter Analysi...mentioning
confidence: 99%
“…The release of plasticizers from a medical device depends on the type of LBP and the storage conditions (temperature and duration) [3][4][5][6][7][8][9]; the higher the temperature and the longer the storage period, the greater the release of DEHP [5,[8][9][10]. The quantity of DEHP released by the medical device also depends on the nature of the LBP [1,4,5,7,9,11].…”
Section: Introductionmentioning
confidence: 99%